Power Relations in Catcalling Behavior among College Students - Rismaningtyas, Fitria (Buana Gender: Jurnal Studi Gender dan Anak, 2025)
This study examines the phenomenon of catcalling in religious college environments. The objectives of the study were to describe catcalling behavior, identify forms of catcalling, and map locations where catcalling occurs in colleges. The study used a mixed-methods approach with data collection through surveys that were further in-depth with interviews. Informants were selected using a purposive sampling technique with the criteria of students who had experienced catcalling. The results of the study showed that catcalling that occurred among students took the form of whistling, excessive greetings, and compliments that were sexual or demeaning. This form of catcalling caused feelings of discomfort, anxiety, and threat to the victim. Catcalling behavior occurs due to a lack of knowledge that such actions are a form of verbal sexual harassment. In addition, other motives found were the urge to be playful, seek attention, and feelings of superiority from the perpetrator towards the victim. The locations where catcalling occurs are generally in public spaces on campus, such as classroom hallways, parking areas, and gazebos. The analysis was conducted using Michel Foucault's theory of power relations to understand the dynamics of power in the context of catcalling, including how social norms, gender structures, and knowledge shape these harassment practices. This study also found a form of resistance from students, both individually and collectively, to the practice of catcalling through critical awareness and reporting to the authorities. This study is expected to be the basis for developing campus policies that are more responsive to the issue of sexual harassment.